2014
DOI: 10.18553/jmcp.2014.20.9.968
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Clinical and Cost Outcomes Associated with Earlier Initiation of Insulin in Patients with Type 2 Diabetes Mellitus

Abstract: As insulin was advanced earlier in therapy in the two-stage and single-stage approaches, patients reaching their A1c targets increased, severe hypoglycemic events increased, and diabetes-related complications and mortality decreased. Cost savings were estimated for 3 (of 4) strategies in the single-stage approach. Delays in treatment escalation substantially reduced patients reaching target A1c levels and increased the occurrence of major nonhypoglycemic diabetic complications. With the exception of substantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The treatment of diabetes complicated with cerebral ischemia-reperfusion injury should combine hypoglycemic drugs with drugs for cerebral ischemia-cerebral injury in a clinical setting. Moreover, adjusting insulin dosage according to the patient's blood glucose levels at any given time often lead to hypoglycemia and exacerbation of the risks of brain ischemia injury [ 37 ]. In addition, nimodipine commonly results in hypotension[ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of diabetes complicated with cerebral ischemia-reperfusion injury should combine hypoglycemic drugs with drugs for cerebral ischemia-cerebral injury in a clinical setting. Moreover, adjusting insulin dosage according to the patient's blood glucose levels at any given time often lead to hypoglycemia and exacerbation of the risks of brain ischemia injury [ 37 ]. In addition, nimodipine commonly results in hypotension[ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…29 In fact, a recent publication based on a Monte Carlo microsimulation model demonstrated that earlier initiation of insulin was associated with a higher proportion of patients achieving their A1c target, decreased risk of diabetes-related complications and death, and cost savings, but an increase in hypoglycemic events. 30 However, the long-term impact of insulin therapy on diabetes-related complications and associated costs remains to be determined. 31 Taken together, these clinical and economic data provide a strong argument for the need for early initiation of insulin therapy in patients with T2DM.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…Alongside the medical consequences for patients with diabetes, clinical inertia also has an impact on healthcare expenditures; overcoming clinical inertia to provide a sustained reduction in HbA1c levels has been associated with significant cost savings and reduced healthcare utilization [ 15 17 ]. Thus, overcoming clinical inertia has the potential to improve both clinical and economic outcomes in T2D patients.…”
Section: Introductionmentioning
confidence: 99%